2004
DOI: 10.1074/jbc.m404802200
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific Activation of the Atrial Natriuretic Factor Promoter by PITX2 and MEF2A

Abstract: The PITX2 homeodomain protein is mutated in patients with Axenfeld-Rieger syndrome and is involved in the development of multiple organ systems, including the heart. We have examined the interaction of PITX2 isoforms with myocyte-enhancing factor 2A (MEF2A), which is a known regulator of cardiac development. A direct interaction between PITX2a and MEF2A was demonstrated using yeast two-hybrid and GST pulldown assays. To study the functional significance of this interaction, we used the atrial natriuretic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
3
15
0
1
Order By: Relevance
“…26 GATAindependent interactions (eg, between dHAND and MEF-2c and between PITX2 and MEF2A) on the ANP gene promoter have also been documented. 27,28 Consistent with the in vitro observations, cardiac-specific deletion of GATA4 results in diminished ANP gene expression and impairment in the hypertrophic response. 29 The rat ANP gene promoter is also regulated by the homeodomain protein Nkx2-5 19,30 and the T box factor Tbx5, 31 both of which have binding sites in the proximal 5Ј flanking sequence of the ANP gene.…”
Section: Transcriptional Regulation Of the Np Genessupporting
confidence: 70%
“…26 GATAindependent interactions (eg, between dHAND and MEF-2c and between PITX2 and MEF2A) on the ANP gene promoter have also been documented. 27,28 Consistent with the in vitro observations, cardiac-specific deletion of GATA4 results in diminished ANP gene expression and impairment in the hypertrophic response. 29 The rat ANP gene promoter is also regulated by the homeodomain protein Nkx2-5 19,30 and the T box factor Tbx5, 31 both of which have binding sites in the proximal 5Ј flanking sequence of the ANP gene.…”
Section: Transcriptional Regulation Of the Np Genessupporting
confidence: 70%
“…1J; supplementary material Table S1). The MEF2 transcription factor is regulated by the p38 MAPK pathway (Han and Molkentin, 2000;Toro et al, 2004). We found a potential MEF2 recognition site in the Irf6 genomic region (Fig.…”
Section: Tgfβ Signaling In the Mee Regulates Irf6 Expression During Pmentioning
confidence: 95%
“…Recent in vitro studies have shown that Pitx2c and Nkx2.5 (a cardiac-specific transcription factors) synergistically regulate the Nppa (atrial natriuretic factor, ANF) promoter. Cotransfection experiments have revealed a role of p38 MAP kinases in up-regulating Pitx2c activation of the ANF promoter in the presence of MEF2A, providing a molecular mechanism for Pitx2c regulation of heart development (Ganga et al, 2003;Toro et al, 2004). Of interest, it has been reported that Pitx2 is a target gene in the Wnt/Dvl2/beta-catenin pathway and operates in specific cell types to control proliferation by regulating expression of the growth control genes cyclin D1, cyclin D2, and c-Myc (Kioussi et al, 2002;Baek et al, 2003).…”
Section: Introductionmentioning
confidence: 99%